2019
DOI: 10.1002/ccd.28457
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous obliteration of the right ventricle to avoid coronary damage by sinusoids in patients with pulmonary atresia intact ventricular septum during staged single ventricle palliation

Abstract: Background and Aims Suprasystemic pressure waves can damage the coronary arteries resulting in myocardial ischemia and excess early mortality. We aimed to reduce the coronary pressure wave through the sinusoids by abolishing RV volume with percutaneous devices. Methods and Results Four patients with PA‐IVS and coronary sinusoids from the hypertensive rudimentary RV were evaluated at a median age 26.6 months (range: 2.7–51.7). Right ventricle coronary dependent flow to the left ventricular myocardium was exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similarly, Hummel et al 14 also reported the emergency coil occlusion of the hypoplastic left ventricle in a critically sick infant with ventriculocoronary connections causing coronary steal and myocardial ischemia. Several studies also detailed the occlusion of the right ventricle in patients with pulmonary atresia, intact ventricular septum and large coronary sinusoids to the right ventricle; which may halt the coronary damage caused by the systolic pressure waves, and thus allow for staged single ventricle palliation in this difficult substrate 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hummel et al 14 also reported the emergency coil occlusion of the hypoplastic left ventricle in a critically sick infant with ventriculocoronary connections causing coronary steal and myocardial ischemia. Several studies also detailed the occlusion of the right ventricle in patients with pulmonary atresia, intact ventricular septum and large coronary sinusoids to the right ventricle; which may halt the coronary damage caused by the systolic pressure waves, and thus allow for staged single ventricle palliation in this difficult substrate 15,16 …”
Section: Discussionmentioning
confidence: 99%